ANALISIS PERBANDINGAN PENERAPAN SAK ETAP DAN PSAK NO. 101 PADA KSU BAITUL MAAL WAT TAMWIL MUJAHIDIN KALIMANTAN BARAT - B51108007, Ade Kurniawan (Jurnal KIAFE, 2013)
Cooperative is an entity consisting of the person or legal entity with bases cooperative activities based on the principle of cooperation as well as economic movement based on the principle of kinship. In conducting its operations, IAI has issued accounting standards in the form of cooperative Entities Financial Accounting Standards No Public Accountability (SAK ETAP). Multipurpose Cooperative Enterprises Baitul Maal Wat Tamwil Mujahadin cooperative legal entity is an entity sharia has presented its financial statements in 2011 based SAK ETAP. Financial statements have been prepared by SAK ETAP although there are some parts that are still referring to the SFAS No.101. The purpose of the study was to determine how the application of SFAS 101 in the financial statements KSU BMT Mujahideen which have been prepared by SAK ETAP. This study uses a case study is descriptive in a way that describes the characteristics of the state and the actual properties of the object of research. The results showed no overall differences between SAK ETAP and SFAS No. 101 at KSU BMT Mujahidin. The difference lies in the different terms used in income statements differ mainly on the load, the notes to the financial statements are statements that are not being met by the SAK ETAP, ie no management in the consolidated financial statements KSU BMT Mujahideen in 2011 on restatement KSU financial statements BMT Mujahideen in 2010 based SAK ETAP. Keywords: Application, Standard, financial statements, cooperative BMT